2022
DOI: 10.3390/foods11101399
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization, UHPLC-Triple-TOF-MS/MS Analysis and Antioxidant Activity of Ceramides from Sea Red Rice Bran

Abstract: As a new type of salt-tolerant rice, sea red rice contains more minerals, proteins, and lipid compounds, and, in particular, its by-product rice bran may be used to replace other commercial rice brans as the main source of ceramides (Cers). However, the extraction rate of Cers is generally low, and it is crucial to seek an efficient extraction method. This study optimized the ultrasonic-assisted extraction of Cers from sea red rice bran using response surface methodology (RSM) and obtained a Cers yield of 12.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The Cers with the highest component content in sea red rice bran were Cer 18:0/24:0 (2OH), Cer 18:0/26:0, Cer 18:0/26:0 (2OH), Cer 18:0/24:0, and Cer 18:0/25:0, which accounted for 23.66, 17.54, 14.91, 11.96, and 7.32, respectively. In vitro oxidation and antiaging experiments have confirmed that Cers from sea red rice bran show good biological activity . Thus, their combined antiaging effects in vivo and their molecular mechanisms are discussed below.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The Cers with the highest component content in sea red rice bran were Cer 18:0/24:0 (2OH), Cer 18:0/26:0, Cer 18:0/26:0 (2OH), Cer 18:0/24:0, and Cer 18:0/25:0, which accounted for 23.66, 17.54, 14.91, 11.96, and 7.32, respectively. In vitro oxidation and antiaging experiments have confirmed that Cers from sea red rice bran show good biological activity . Thus, their combined antiaging effects in vivo and their molecular mechanisms are discussed below.…”
Section: Resultsmentioning
confidence: 93%
“…Based on our previous research, the Cer compounds in sea red rice bran were analyzed using UHPLC-Triple-TOF-MS/MS, and the data were integrated. We found that it contained 46 different Cer types . The sample was injected 1 μg at a time, and the internal standard method was used for quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations